Treatment of posterior Benign Paroxysmal Positional Vertigo is efficient and safe with a new Mechanical Rotational Chair - Hougaard, Dan Dupont; Duch, Kirsten; Bech, Mathias Winther (Frontiers in Neurology, 2023)
Background Benign paroxysmal positional vertigo (BPPV) is the most predominant vestibular disease. Previously, in the management of BPPV, both therapeutic and diagnostic benefits with mechanical rotation chairs (MRCs) have been reported. However, no previous studies have examined the efficacy of MRC treatment with a fairly new MRC. Methods Randomized three-armed parallel open-labeled prospective clinical trial. One hundred and five patients diagnosed with posterior BPPV underwent diagnostics and treatment with an MRC. Patients were randomized to either a Semont maneuver, an Epley maneuver or a 360-degree backwards somersault maneuver. Primary endpoint was to evaluate the efficiency of an MRC in the treatment of posterior BPPV with three separate treatment modalities. Secondary objectives included subjective vertigo assessments. Results BPPV treatment with this MRC is very efficient with success rates up to 97.1 percent. The number of treatments required to achieve complete resolution of both objective findings and subjective symptoms was 1.5. Almost 47 percent of patients experienced complete resolution of both subjective and objective measures following one (first) treatment. All Dizziness Handicap Inventory scores decreased significantly post-treatment. Conclusion Treatment of posterior BPPV, with the MRC used in this study, was very efficient with both the Semont, the Epley, and the 360-degree backwards somersault maneuver. Based on the findings in this study, this fairly new MRC seems both effective and safe to use.